ANALYSIS THE IMPLEMENTATION OF ISLAMIC STORE ATTRIBUTES AND MARKETING MIX FROM ISLAMIC PERSPECTIVE (Survey at La-Tansa Gontor Department Store Ponorogo) - Faisal Setiawan Fajri; Hamidah Tussifah (Islamic Business and Management Journal, 2018)
This arrangement aims to find out the Implementation of Islamic store attributes and marketing mix from Islamic perspective at La-Tansa Gontor Department Store. Implementation of Islamic store attributes and marketing mix from the Islamic perspective in the store is highly recommended that Muslim business people still maintain the norms of religion in business and establish a business strategy in accordance with Islamic Shari'a.La-Tansa Gontor Departement Store is one business unit owned by Darussalam Gontor Islamic Boarding School which aims to get the profit used for development and meet all the needs of Darussalam Gontor Islamic Boarding School. In addition, the establishment of La-Tansa Gontor aims for educational means for teachers of Darussalam Gontor Islamic Boarding School and as a means of dakwah for the employees and the community. This arrangement raises the formulation of the problem: does La-Tansa Gontor Department Store have implemented Islamic Store Attributes and marketing mix from Islamic perspective? With a qualitative approach, data collection with observation, interview and documentation techniques. The data analysis used is descriptive analysis technique with the aim to describe the data that researcher collect about Implementation of Islamic store attributes and marketing mix from Islamic perspective in La-Tansa Gontor Department Store.Keywords: Islamic Store Attributes and marketing mix from Islamic perspective, La-Tansa Gontor Department Store.